The Diversification of Employment Towards the Socioeconomic Resilience of Local Communities Around the PT. VDNI Nickel Smelter : A Study in Morosi District, Konawe Regency, Southeast Sulawesi Province - Asrani; Nur Azisyah Mukmin (Universitas Halu Oleo (UHO), 2025)
This study examines the diversification of employment in strengthening the socioeconomic resilience of local communities living around the PT. VDNI nickel smelter in Morosi. Economic dependency predominantly on the mining sector increases community vulnerability to commodity price fluctuations and policy changes affecting the industry. Using a qualitative descriptive approach, data were collected through field observations and in-depth interviews with residents of Morosi District to analyze the impact of employment diversification on their socioeconomic stability. The findings indicate that employment diversification contributes to enhancing economic stability and strengthening community social bonds, helping communities adapt more effectively to economic changes. These results support the theory of socioeconomic resilience, highlighting the importance of supplementary income and robust social connections in navigating economic uncertainties. The study concludes by recommending government and corporate support through training programs and the development of new economic sectors to achieve long-term sustainability.